Preparation method and application of starch-based ionic porous polymer
By functionalizing ionic liquid on the starch molecular chain, the high-specific surface starch-based ionic porous polymer is constructed, and the problem of difficult degradation of existing porous materials after adsorption of formaldehyde is solved, achieving efficient and stable formaldehyde adsorption and degradable environmental protection is achieved. Effect.
Patent Information
- Application Number
- CN202411661337.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-11-20
AI Technical Summary
Existing porous materials are difficult to degrade after adsorbing formaldehyde, resulting in the waste adsorbent becoming hazardous waste and polluting the environment.
By functionalizing the ionic liquid on the starch molecular chain, a high-specific surface starch-based ionic porous polymer is constructed, and the selective capture of formaldehyde is achieved using the adsorption microenvironment of the alkaline ionic liquid.
It has achieved efficient adsorption of formaldehyde, stable material structure and stable physical and chemical properties, and can be degraded through microbial degradation to avoid secondary contamination of waste adsorbents.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the field of novel functional materials, and in particular relates to a method for preparing a starch-based ionic porous polymer capable of absorbing formaldehyde. Background Art
[0002] Formaldehyde (HCHO) is one of the main volatile organic compounds (VOCs). It is widely used in materials in the fields of anti-corrosion, textiles, wood processing, coatings, etc., and is emitted into the air. Long-term exposure to formaldehyde environment, even at low concentrations (<0.1mg / m 3 ), can also cause nasal tumors, nasopharyngeal cancer and skin irritation. Therefore, it is of key significance and importance to effectively remove formaldehyde under atmospheric conditions to improve the air quality in enclosed spaces such as bedrooms, offices, and cars.
[0003] Due to the high removal rate, high cost-effectiveness, and low energy consumption of the adsorption method, it is considered to be a particularly suitable method for treating formaldehyde. At present, the aldehyde VOCs adsorbents widely used in industry are mainly some porous materials with high specific surface areas, such as activated carbon, molecular sieves, etc. However, after a certain period of use, such adsorbent materials will be transformed into "VOCs waste adsorbents", and even after the VOCs are removed, they are clearly identified as hazardous waste. If LOE degradable porous materials can be designed and prepared for the capture of aldehyde VOCs, they can be harmlessly treated through full microbial degradation after adsorption, thereby avoiding secondary hazardous waste pollution caused by existing inorganic porous materials, and have certain ecological and economic value.
[0004] Among the numerous biodegradable materials, natural starch is the second largest renewable natural biomass resource on earth after cellulose. It has the advantages of abundant sources, low price, and green environmental protection. It has attracted widespread attention from researchers in recent years. Research reports show that starch-based polymer materials (such as starch-based plastics) can be completely and quickly degraded by microorganisms in nature, and the final degradation products can be recycled through plant photosynthesis without causing any pollution to the environment. If adsorbents made of such materials are used to adsorb VOCs, the problem of the difficulty in degrading waste adsorbents can be solved. Summary of the invention
[0005] In view of the deficiencies of the prior art, the purpose of the present invention is to provide a method for preparing a green, high-specific-surface, and highly efficient starch-based ionic porous polymer for adsorbing formaldehyde. The ionic liquid is chemically bonded to the starch molecular chain, and acts as a cross-linking reaction site to produce a strong chemical reaction with the cross-linking agent molecule, thereby increasing the cross-linking strength of the cross-linking agent on the starch molecular chain and constructing a starch-based ionic porous material with a high specific surface area. At the same time, the alkaline groups of the ionic liquid can construct an alkaline adsorption microenvironment in the pores of the starch-based ionic porous polymer, thereby achieving the selective capture of aldehyde VOCs.
[0006] The purpose of the present invention is achieved through the following technical solutions:
[0007] A method for preparing a starch-based ionic porous polymer and its application, the method comprising the following steps:
[0008] (1) Preparation of lactic acid-starch: gelatinize starch at a certain temperature, add lactic acid and catalyst zinc acetate to continue the reaction for 10-12 hours, cool after the reaction is completed, add ethanol to precipitate white solid, filter, extract with ethanol, and freeze-dry to obtain lactic acid-starch;
[0009] (2) Preparation of ionic liquid functionalized starch: 2 Under atmosphere protection, the lactic acid-starch, ionic liquid and initiator azobisisobutyronitrile obtained in (1) are dispersed in an aqueous solution, stirred and reacted for 20-24 hours, and after the reaction is completed and cooled, ethanol is added to precipitate a white solid, which is filtered and freeze-dried to obtain ionic liquid functionalized starch;
[0010] (3) Preparation of starch-based ionic porous polymers: 2 Under the protection of the atmosphere, the ionic liquid functionalized starch and the crosslinking agent obtained in (2) were added to 1,2-dichloroethane, and then the catalyst anhydrous FeCl 3 After stirring at 40-45°C for 2-3h, the temperature was raised to 80-85°C and the reaction was continued for 16-20h. After the reaction was completed and cooled, the mixture was filtered, extracted with methanol, and dried in vacuo to obtain a starch-based ionic porous polymer.
[0011] As a further preferred embodiment of the present technical solution, the starch in step (1) is cassava starch, sweet potato starch or corn starch.
[0012] As a further preferred embodiment of the present technical solution, in step (1), the mass ratio of starch, lactic acid and catalyst zinc acetate is 1:0.2-3:0.02-0.1.
[0013] As a further preferred embodiment of the present technical solution, in step (1), the starch is first gelatinized at 70-85° C. for 30-60 min.
[0014] As a further preferred embodiment of the present technical solution, the ionic liquid in step (1) is 1-vinyl-3-butyl imidazole bromide [C 4 VIm][Br], 1-vinyl-3-butyl imidazole tetrafluoroborate [C 4 VIm][BF 4 ], 1-vinyl-3-butyl imidazole hexafluorophosphate [C 4 VIm][PF 6 ] and 1-vinyl-3-butyl imidazole acetate [C 4Any one of VIm][OAc].
[0015] As a further preferred embodiment of the present technical solution, in the step (2), the mass ratio of lactic acid-starch, ionic liquid and initiator azobisisobutyronitrile is 1:1-5:0.02-0.1.
[0016] As a further preferred embodiment of the present technical solution, the cross-linking agent in step (3) is biphenyl dichlorobenzyl or p-dichlorobenzyl.
[0017] As a further preferred embodiment of the present technical solution, in step (3), the ionic liquid functionalized starch, the crosslinking agent and the catalyst anhydrous FeCl 3 The mass ratio is 1:0.5-3:0.2-2.
[0018] As a further preferred embodiment of the present technical solution, in step (3), the plastomeric ratio of the ionic liquid functionalized starch to 1,2-dichloroethane is 1:50-150.
[0019] The starch-based ionic porous polymer prepared by the method of the present invention is used in an aldehyde VOCs adsorbent.
[0020] The starch-based ionic porous polymer of the present invention is applied to the field of aldehyde VOCs adsorption and separation to produce highly efficient adsorption of formaldehyde.
[0021] The invention comprises the following steps: firstly, starch is modified by lactic acid through an esterification reaction under the action of zinc acetate as a catalyst to obtain lactic acid-starch (ST-LA); then, an ionic liquid containing a double bond is highly reacted with lactic acid free radicals under the action of an initiator using lactic acid as a connecting molecule, so that the ionic liquid can be covalently bonded to the starch molecular chain to obtain ionic liquid functionalized starch (ST-LA-IL); finally, N 2 Under the protection of the atmosphere, ST-LA-IL, crosslinker, and 1,2-dichloroethane were mixed evenly, and then anhydrous FeCl 3 , inducing Friedel-Crafts alkylation reaction, the reaction was carried out under heating conditions to obtain a brown solid, which was then filtered, Soxhlet extracted and vacuum dried to obtain a starch-based ionic porous polymer (H-ST-LA-IL).
[0022] Principle of the present invention: In view of the fact that the skeleton of traditional starch-based porous materials is easy to collapse and the specific surface area is low, which is far from meeting the actual demand for gas adsorption and capture, the present invention proposes an alkaline ionic liquid immobilization strategy, and uses ionic liquid to functionally modify the starch chain to provide effective cross-linking sites for post-cross-linking, forming a high-strength, high-specific surface area adsorption network. The ionic liquid is anchored to the starch molecular chain through chemical bonds, and the imidazole group it carries can produce a strong chemical reaction with the cross-linking agent molecules, thereby increasing the cross-linking strength of the cross-linking agent on the starch molecular chain and constructing a high-specific surface starch-based ionic porous polymer. At the same time, the binding sites of the alkaline ionic liquid are used to enhance the adsorption performance of formaldehyde.
[0023] Compared with the prior art, the present invention has the following advantages:
[0024] 1. The present invention utilizes lactic acid grafted starch, which can not only effectively release the high-density entanglement between starch chains, but also successfully modify the lactic acid active sites on the starch chains, which is beneficial to the grafting of ionic liquids.
[0025] 2. The starch-based ionic porous polymer prepared by the present invention is used for formaldehyde adsorption. The material has a stable structure and stable physical and chemical properties. It not only solves the problem of easy collapse of the material skeleton, but also facilitates the recovery and recycling of the adsorbent.
[0026] 3. The starch-based ionic porous polymer prepared by the present invention allows the alkaline ionic liquid to be successfully intercalated into the cross-linked network of the starch-based polymer, which not only increases the specific surface area of the starch-based polymer, but also strengthens the adsorption process of formaldehyde.
[0027] 4. The present invention utilizes ionic liquid as a formaldehyde adsorption site, and the starch-based ionic porous polymer constructed has excellent formaldehyde adsorption performance. The formaldehyde adsorption test results show that the starch-based ionic porous polymer formed by ionic liquid intercalation starch molecular chains has excellent adsorption performance for low-concentration formaldehyde (350ppm), and its formaldehyde adsorption capacity is about 13.5mg / g. The formaldehyde adsorption capacity of starch-based non-ionic porous polymer and pure starch-based polymer is only 6.9mg / g and 4.5mg / g.
[0028] 5. The starch-based ionic porous polymer prepared by the present invention is green, environmentally friendly, biodegradable, low-cost, and suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 These are infrared spectra of original cassava starch, lactic acid-cassava starch, ionic liquid functionalized cassava starch and the starch-based ionic porous polymer prepared in Example 8.
[0030] Figure 2SEM images of the starch-based non-ionic porous polymer (H-ST-g-PS) prepared in Comparative Example 1, the starch-based polymer (H-ST) prepared in Comparative Example 2, and the starch-based ionic porous polymer (H-ST-LA-IL) prepared in Example 8 of the present invention.
[0031] Figure 3 XRD patterns of the starch-based nonionic porous polymer (H-ST-g-PS) prepared in Comparative Example 1, the starch-based polymer (H-ST) prepared in Comparative Example 2, and the starch-based ionic porous polymer (H-ST-LA-IL) prepared in Example 8 of the present invention.
[0032] Figure 4 Nitrogen adsorption / desorption isotherms and pore size distribution curves of the starch-based non-ionic porous polymer (H-ST-g-PS) prepared in Comparative Example 1, the starch-based polymer (H-ST) prepared in Comparative Example 2, and the starch-based ionic porous polymer (H-ST-LA-IL) prepared in Example 8 of the present invention.
[0033] Figure 5 It is a graph showing the adsorption kinetics of formaldehyde by the starch-based non-ionic porous polymer (H-ST-g-PS) prepared in Comparative Example 1, the starch-based polymer (H-ST) prepared in Comparative Example 2, and the starch-based ionic porous polymer (H-ST-LA-IL) prepared in Example 8 of the present invention.
[0034] Figure 6 It is a graph showing the adsorption rate of formaldehyde by the starch-based non-ionic porous polymer (H-ST-g-PS) prepared in Comparative Example 1, the starch-based polymer (H-ST) prepared in Comparative Example 2, and the starch-based ionic porous polymer (H-ST-LA-IL) prepared in Example 8 of the present invention. DETAILED DESCRIPTION
[0035] The following further examples are given to illustrate the present invention in detail. It should be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples in a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description of this article, and are not limited to the specific values exemplified below.
[0036] Example 1
[0037] A method for preparing a starch-based ionic porous polymer and its application, comprising the following steps:
[0038] (1) Preparation of lactic acid-cassava starch: 5 g of cassava starch was dispersed in 100 mL of deionized water, and the starch was gelatinized at 80° C. for half an hour. Then, 10 g of lactic acid and 0.2 g of catalyst zinc acetate were added and the reaction was continued for 12 h. After the reaction was completed and cooled, 200 mL of ethanol was added to precipitate a white solid. After suction filtration, ethanol Soxhlet extraction for 24 h, and freeze-drying, lactic acid-cassava starch was obtained.
[0039] (2) Preparation of ionic liquid functionalized cassava starch: 2 Under atmosphere protection, 2 g of lactic acid-cassava starch obtained in (1), 4 g of 1-vinyl-3-butylimidazolium bromide, and 0.15 g of initiator azobisisobutyronitrile were dispersed in 50 mL of deionized water, heated and stirred for reaction for 24 h, and after the reaction was completed and cooled, 200 mL of ethanol was added to precipitate a white solid, which was filtered and freeze-dried to obtain ionic liquid functionalized cassava starch.
[0040] (3) Preparation of starch-based ionic porous polymers: 2 Under the protection of the atmosphere, 1 g of ionic liquid functionalized cassava starch obtained in (2) and 1 g of crosslinking agent diphenylbenzyl chloride were added to 100 mL of 1,2-dichloroethane, and then 2 g of catalyst anhydrous FeCl 3 After stirring at 45 °C for 2 h, the temperature was raised to 80 °C and the reaction was continued for 20 h. After the reaction was completed and cooled, the mixture was filtered, extracted with methanol Soxhlet for 24 h, and vacuum dried to obtain a starch-based ionic porous polymer (H-ST-LA-IL).
[0041] Example 2
[0042] A method for preparing a starch-based ionic porous polymer and its application, comprising the following steps:
[0043] (1) Preparation of lactic acid-cassava starch: 5 g of cassava starch was dispersed in 100 mL of deionized water, and the starch was gelatinized at 80°C for 60 min. Then, 10 g of lactic acid and 0.2 g of catalyst zinc acetate were added and the reaction continued for 10 h. After the reaction was completed and cooled, 200 mL of ethanol was added to precipitate a white solid. The lactic acid-cassava starch was obtained after filtration, ethanol Soxhlet extraction for 24 h, and freeze-drying.
[0044] (2) Preparation of ionic liquid functionalized cassava starch: 2 Under atmosphere protection, 2 g of lactic acid-cassava starch obtained in (1), 4 g of 1-vinyl-3-butyl imidazole tetrafluoroborate, and 0.15 g of initiator diisobutylene were dispersed in 50 mL of deionized water, heated and stirred for reaction for 20 h, and after the reaction was completed and cooled, 200 mL of ethanol was added to precipitate a white solid, which was filtered and freeze-dried to obtain ionic liquid functionalized cassava starch.
[0045] (3) Preparation of starch-based ionic porous polymers: 2 Under the protection of the atmosphere, 1 g of ionic liquid functionalized cassava starch obtained in (2) and 1 g of crosslinking agent diphenylbenzyl chloride were added to 100 mL of 1,2-dichloroethane, and then 2 g of catalyst anhydrous FeCl 3 After stirring at 40 °C for 3 h, the temperature was raised to 85 °C and the reaction was continued for 16 h. After the reaction was completed and cooled, the mixture was filtered, extracted with methanol Soxhlet for 24 h, and vacuum dried to obtain a starch-based ionic porous polymer (H-ST-LA-IL).
[0046] Example 3
[0047] A method for preparing a starch-based ionic porous polymer and its application, comprising the following steps:
[0048] (1) Preparation of lactic acid-cassava starch: 5 g of cassava starch was dispersed in 100 mL of deionized water, and the starch was gelatinized at 80° C. for half an hour. Then, 10 g of lactic acid and 0.2 g of catalyst zinc acetate were added and the reaction was continued for 12 h. After the reaction was completed and cooled, 200 mL of ethanol was added to precipitate a white solid. The lactic acid-cassava starch was obtained after filtration, ethanol Soxhlet extraction for 24 h, and freeze-drying.
[0049] (2) Preparation of ionic liquid functionalized cassava starch: 2 Under atmosphere protection, 2 g of lactic acid-cassava starch obtained in (1), 4 g of 1-vinyl-3-butylimidazole hexafluorophosphate, and 0.15 g of initiator azobisisobutyronitrile were dispersed in 50 mL of deionized water, heated and stirred for reaction for 24 h, and after the reaction was completed and cooled, 200 mL of ethanol was added to precipitate a white solid, which was filtered and freeze-dried to obtain ionic liquid functionalized cassava starch.
[0050] (3) Preparation of starch-based ionic porous polymers: 2 Under the protection of the atmosphere, 1 g of ionic liquid functionalized cassava starch obtained in (2) and 1 g of crosslinking agent diphenylbenzyl chloride were added to 100 mL of 1,2-dichloroethane, and then 2 g of catalyst anhydrous FeCl 3 After stirring at 45 °C for 2 h, the temperature was raised to 80 °C and the reaction was continued for 20 h. After the reaction was completed and cooled, the mixture was filtered, extracted with methanol Soxhlet for 24 h, and vacuum dried to obtain a starch-based ionic porous polymer (H-ST-LA-IL).
[0051] Example 4
[0052] A method for preparing a starch-based ionic porous polymer and its application, comprising the following steps:
[0053] (1) Preparation of lactic acid-cassava starch: 5 g of cassava starch was dispersed in 100 mL of deionized water, and the starch was gelatinized at 80° C. for half an hour. Then, 10 g of lactic acid and 0.2 g of catalyst zinc acetate were added and the reaction was continued for 12 h. After the reaction was completed and cooled, 200 mL of ethanol was added to precipitate a white solid. The lactic acid-cassava starch was obtained after filtration, ethanol Soxhlet extraction for 24 h, and freeze-drying.
[0054] (2) Preparation of ionic liquid functionalized cassava starch: 2 Under atmosphere protection, 2 g of lactic acid-cassava starch, 4 g of 1-vinyl-3-butyl imidazole acetate, and 0.15 g of initiator azobisisobutyronitrile obtained in (1) were dispersed in 50 mL of deionized water, heated and stirred to react for 24 h, and after the reaction was completed and cooled, 200 mL of ethanol was added to precipitate a white solid, which was filtered and freeze-dried to obtain ionic liquid functionalized cassava starch.
[0055] (3) Preparation of starch-based ionic porous polymers: 2 Under the protection of the atmosphere, 1 g of ionic liquid functionalized cassava starch obtained in (2) and 1 g of crosslinking agent diphenylbenzyl chloride were added to 100 mL of 1,2-dichloroethane, and then 2 g of catalyst anhydrous FeCl 3 After stirring at 45 °C for 2 h, the temperature was raised to 80 °C and the reaction was continued for 20 h. After the reaction was completed and cooled, the mixture was filtered, extracted with methanol Soxhlet for 24 h, and vacuum dried to obtain a starch-based ionic porous polymer (H-ST-LA-IL).
[0056] Example 5
[0057] A method for preparing a starch-based ionic porous polymer and its application, comprising the following steps:
[0058] (1) Preparation of lactic acid-cassava starch: 5 g of cassava starch was dispersed in 100 mL of deionized water, and the starch was gelatinized at 85° C. for half an hour. Then, 10 g of lactic acid and 0.2 g of zinc acetate as a catalyst were added and the reaction was continued for 10 h. After the reaction was completed and cooled, 200 mL of ethanol was added to precipitate a white solid. The lactic acid-cassava starch was obtained after filtration, ethanol Soxhlet extraction for 24 h, and freeze-drying.
[0059] (2) Preparation of ionic liquid functionalized cassava starch: 2 Under atmosphere protection, 2 g of lactic acid-cassava starch obtained in (1), 4 g of 1-vinyl-3-butylimidazolium bromide, and 0.15 g of initiator azobisisobutyronitrile were added to 50 mL of deionized water, heated and stirred for reaction for 20 h, and after the reaction was completed and cooled, 200 mL of ethanol was added to precipitate a white solid, which was filtered and freeze-dried to obtain ionic liquid functionalized cassava starch.
[0060] (3) Preparation of starch-based ionic porous polymers: 2 Under the protection of the atmosphere, 1 g of ionic liquid functionalized cassava starch obtained in (2) and 1 g of cross-linking agent p-dichlorobenzyl were added to 100 mL of 1,2-dichloroethane, and then 2 g of catalyst anhydrous FeCl 3 After stirring at 40 °C for 3 h, the temperature was raised to 85 °C and the reaction was continued for 16 h. After the reaction was completed and cooled, the mixture was filtered, extracted with methanol Soxhlet for 24 h, and vacuum dried to obtain a starch-based ionic porous polymer (H-ST-LA-IL).
[0061] Example 6
[0062] A method for preparing a starch-based ionic porous polymer and its application, comprising the following steps:
[0063] (1) Preparation of lactic acid-cassava starch: 5 g of cassava starch was dispersed in 100 mL of deionized water, and the starch was gelatinized at 80° C. for half an hour. Then, 10 g of lactic acid and 0.2 g of catalyst zinc acetate were added and the reaction was continued for 12 h. After the reaction was completed and cooled, 200 mL of ethanol was added to precipitate a white solid. The lactic acid-cassava starch was obtained after filtration, ethanol Soxhlet extraction for 24 h, and freeze-drying.
[0064] (2) Preparation of ionic liquid functionalized cassava starch: 2 Under atmosphere protection, 2 g of lactic acid-cassava starch obtained in (1), 4 g of 1-vinyl-3-butyl imidazole tetrafluoroborate, and 0.15 g of initiator azobisisobutyronitrile were dispersed in 50 mL of deionized water, heated and stirred for reaction for 24 h, and after the reaction was completed and cooled, 200 mL of ethanol was added to precipitate a white solid, which was filtered and freeze-dried to obtain ionic liquid functionalized cassava starch.
[0065] (3) Preparation of starch-based ionic porous polymers: 2 Under the protection of the atmosphere, 1 g of ionic liquid functionalized cassava starch obtained in (2) and 1 g of cross-linking agent p-dichlorobenzyl were added to 100 mL of 1,2-dichloroethane, and then 2 g of catalyst anhydrous FeCl 3 After stirring at 45 °C for 2 h, the temperature was raised to 80 °C and the reaction was continued for 20 h. After the reaction was completed and cooled, the mixture was filtered, extracted with methanol Soxhlet for 24 h, and vacuum dried to obtain a starch-based ionic porous polymer (H-ST-LA-IL).
[0066] Example 7
[0067] A method for preparing a starch-based ionic porous polymer and its application, comprising the following steps:
[0068] (1) Preparation of lactic acid-cassava starch: 5 g of cassava starch was dispersed in 100 mL of deionized water, and the starch was gelatinized at 80° C. for half an hour. Then, 10 g of lactic acid and 0.2 g of catalyst zinc acetate were added and the reaction was continued for 12 h. After the reaction was completed and cooled, 200 mL of ethanol was added to precipitate a white solid. The lactic acid-cassava starch was obtained after filtration, ethanol Soxhlet extraction for 24 h, and freeze-drying.
[0069] (2) Preparation of ionic liquid functionalized cassava starch: 2 Under atmosphere protection, 2 g of lactic acid-cassava starch obtained in (1), 4 g of 1-vinyl-3-butylimidazole hexafluorophosphate, and 0.15 g of initiator azobisisobutyronitrile were dispersed in 50 mL of deionized water, heated and stirred for reaction for 24 h, and after the reaction was completed and cooled, 200 mL of ethanol was added to precipitate a white solid, which was filtered and freeze-dried to obtain ionic liquid functionalized cassava starch.
[0070] (3) Preparation of starch-based ionic porous polymers: 2 Under the protection of the atmosphere, 1 g of ionic liquid functionalized cassava starch obtained in (2) and 1 g of cross-linking agent p-dichlorobenzyl were added to 100 mL of 1,2-dichloroethane, and then 2 g of catalyst anhydrous FeCl 3 After stirring at 45 °C for 2 h, the temperature was raised to 80 °C and the reaction was continued for 20 h. After the reaction was completed and cooled, the mixture was filtered, extracted with methanol Soxhlet for 24 h, and vacuum dried to obtain a starch-based ionic porous polymer (H-ST-LA-IL).
[0071] Example 8
[0072] A method for preparing a starch-based ionic porous polymer and its application, comprising the following steps:
[0073] (1) Preparation of lactic acid-cassava starch: 5 g of cassava starch was dispersed in 100 mL of deionized water, and the starch was gelatinized at 80° C. for half an hour. Then, 10 g of lactic acid and 0.2 g of catalyst zinc acetate were added and the reaction was continued for 12 h. After the reaction was completed and cooled, 200 mL of ethanol was added to precipitate a white solid. The lactic acid-cassava starch was obtained after filtration, ethanol Soxhlet extraction for 24 h, and freeze-drying.
[0074] (2) Preparation of ionic liquid functionalized cassava starch: 2 Under atmosphere protection, 2 g of lactic acid-cassava starch, 4 g of 1-vinyl-3-butyl imidazole acetate, and 0.15 g of initiator azobisisobutyronitrile obtained in (1) were dispersed in 50 mL of deionized water, heated and stirred to react for 24 h, and after the reaction was completed and cooled, 200 mL of ethanol was added to precipitate a white solid, which was filtered and freeze-dried to obtain ionic liquid functionalized cassava starch.
[0075] (3) Preparation of starch-based ionic porous polymers: 2 Under the protection of the atmosphere, 1 g of ionic liquid functionalized cassava starch obtained in (2) and 1 g of cross-linking agent p-dichlorobenzyl were added to 100 mL of 1,2-dichloroethane, and then 2 g of catalyst anhydrous FeCl 3 After stirring at 45 °C for 2 h, the temperature was raised to 80 °C and the reaction was continued for 20 h. After the reaction was completed and cooled, the mixture was filtered, extracted with methanol Soxhlet for 24 h, and vacuum dried to obtain a starch-based ionic porous polymer (H-ST-LA-IL).
[0076] Comparative Example 1
[0077] A method for preparing a starch-based nonionic porous polymer comprises the following steps:
[0078] (1) Preparation of styrene-functionalized cassava starch (ST-g-PS): 5 g of cassava starch was dispersed in 100 mL of deionized water, and the starch was gelatinized at 80°C for half an hour. Then, 10 g of styrene and 0.2 g of initiator ammonium persulfate were added and the reaction was continued for 6 h. After the reaction was completed and cooled, 200 mL of ethanol was added to precipitate a white solid. After filtration, Soxhlet extraction with a mixed solvent of cyclohexane and acetone (cyclohexane: acetone = 3:1) for 24 h, and freeze-drying, styrene-cassava starch was obtained.
[0079] (2) Preparation of starch-based nonionic porous polymer (H-ST-g-PS): 2 Under the protection of the atmosphere, 1 g of styrene-functionalized cassava starch obtained in (1) and 0.5 g of cross-linking agent p-dichlorobenzyl were added to 100 mL of 1,2-dichloroethane, and then 2 g of anhydrous FeCl 3 After stirring at 45 °C for 2 h, the temperature was raised to 80 °C and the reaction was continued for 20 h. After the reaction was completed and cooled, the mixture was filtered, extracted with methanol Soxhlet for 24 h, and vacuum dried to obtain a starch-based non-ionic porous polymer (H-ST-g-PS).
[0080] Comparative Example 2
[0081] Preparation of pure starch-based polymer (H-ST): 2 Under the protection of the atmosphere, 1g of cassava starch and 1g of cross-linking agent benzyl dichloride were added to 100mL of 1,2-dichloroethane, and then 2g of catalyst anhydrous FeCl 3 After stirring at 45 °C for 2 h, the temperature was raised to 80 °C and the reaction was continued for 20 h. After the reaction was completed and cooled, the mixture was filtered, extracted with methanol Soxhlet for 24 h, and vacuum dried to obtain pure starch-based polymer (H-ST).
[0082] Material performance test:
[0083] The products prepared in comparative example 1, comparative example 2 and some embodiments of the present invention were subjected to structural and performance characterization analysis.
[0084] (I) FT-IR characterization of starch-based ionic porous polymers
[0085] Figure 3 The infrared spectra of raw cassava starch (Starch), lactic acid-cassava starch (ST-LA), ionic liquid functionalized cassava starch (ST-LA-IL) and starch-based ionic porous polymer (H-ST-LA-IL) are shown (FTS3000 infrared spectrometer scanner from BIO-RAD, USA). Starch, ST-LA, ST-LA-IL and H-ST-LA-IL have a wavelength of 3400 cm -1 There is a strong absorption peak at 1732cm, which is formed by the hydrogen bonding of the OH peaks in the starch molecules. Compared with the Starch spectrum, the intensity of the absorption peak of ST-LA is weakened. It can be inferred that the hydroxyl groups of starch are partially replaced. -1 A sharp and obvious absorption peak appears at 1549cm, which is the characteristic peak of C=O stretching vibration in the ester group. -1 The peaks at 3024 cm-1 are the characteristic peaks of C=N and C=C stretching vibrations of the imidazole ring of the ionic liquid in ST-LA-IL. -1 The Ar-H stretching vibration peak at indicates that the cross-linking agent dichlorobenzyl successfully cross-linked.
[0086] (ii) Surface morphology of polymers
[0087] The surface morphology of the cassava starch (Starch), the starch-based nonionic porous polymer (H-ST-g-PS) prepared in Comparative Example 1, the pure starch-based polymer (H-ST) prepared in Comparative Example 2, and the starch-based ionic porous polymer (H-ST-LA-IL) prepared in Example 8 of the present invention were characterized by a Japanese Hitachi S-3400N low-power scanning electron microscope. Figure 1 As shown. The surface of cassava starch particles is very smooth, and it can be seen that the surface of H-ST-g-PS prepared in Comparative Example 1 is rough, showing a disordered and messy structure. In the SEM image of Comparative Example 2, the presence of starch granules can be clearly seen, indicating that the H-ST synthesized according to Comparative Example 2 is a mixture of starch granules and cross-linking agent dichlorobenzyl self-polymers, and the starch has not been successfully polymerized. This may be due to the lack of polymerization reaction functional groups on the surface of the unmodified starch, resulting in the failure of the polymerization reaction. The H-ST-LA-IL prepared in Example 8 of the present invention has a clear lamellar structure, which can expose formaldehyde adsorption sites to the greatest extent and improve the formaldehyde adsorption capacity.
[0088] (III) XRD characterization of polymers
[0089] The crystal structures of cassava starch (Starch), the starch-based non-ionic porous polymer (H-ST-g-PS) prepared in Comparative Example 1, the pure starch-based polymer (H-ST) prepared in Comparative Example 2, and the starch-based ionic porous polymer (H-ST-LA-IL) prepared in Example 8 of the present invention were characterized by using Japanese RIGAKU SMARTLAB3KW powder X-ray diffraction (PXRD) with CuKα radiation in the range of 2θ=5-60°, as shown in FIG. Figure 2 It can be clearly seen that both H-ST-g-PS and H-ST-LA-IL show characteristic amorphous carbon peaks, while H-ST still retains some of the original starch crystals, indicating that the starch has not been successfully polymerized, which is consistent with the SEM results.
[0090] (IV) Characterization of nitrogen adsorption / desorption isotherms and pore structure parameters of polymers
[0091] The specific surface area and pore structure of the starch-based nonionic porous polymer (H-ST-g-PS) prepared in Comparative Example 1, the pure starch-based polymer (H-ST) prepared in Comparative Example 2, and the starch-based ionic porous polymer (H-ST-LA-IL) prepared in the present invention were characterized at 77K using an American Micromeritics ASAP 2460 specific surface and porosity analyzer. The characterization results are shown in Figure 2. Figure 4 As shown in Table 1, Example 8 is the material with the best parameters.
[0092] Table 1 Specific surface area and pore structure parameters of polymer materials
[0093]
[0094] Depend on Figure 4 Pore size analysis shows that the pore sizes of H-ST-g-PS, H-ST, and H-ST-LA-IL are concentrated in It matches the size of formaldehyde molecules and is beneficial for formaldehyde adsorption. By comparing Example 4 with Example 8, it can be seen that the micropore specific surface area ratio of H-ST-LA-IL prepared by the cross-linking agent p-dichlorobenzyl in Example 8 is as high as 0.78, which is much higher than the H-ST-LA-IL prepared by the cross-linking agent biphenyl dichlorobenzyl in Example 4. It shows that the H-ST-LA-IL prepared by the cross-linking agent p-dichlorobenzyl contains a richer microporous structure, which is more conducive to formaldehyde adsorption. Compared with the H-ST-g-PS prepared in Comparative Example 1 and the H-ST prepared in Comparative Example 2, the BET specific surface area, micropore specific surface area, and mesopore specific surface area of the H-ST-LA-IL prepared in Example 8 of the present invention have increased, and the pore volume of micropores and mesopores has also increased, creating good conditions for adsorption.
[0095] (V) Analysis of the adsorption kinetics of formaldehyde by polymers.
[0096] The adsorption kinetics of low-concentration formaldehyde (350 ppm) were measured using a Finnish GASERA ONE photoacoustic spectrometer multi-gas analyzer for the starch-based non-ionic porous polymer (H-ST-g-PS) prepared in Comparative Example 1, the pure starch-based polymer (H-ST) prepared in Comparative Example 2, and the starch-based ionic porous polymer (H-ST-LA-IL) prepared in the present invention. Figure 5 The adsorption kinetics of formaldehyde on H-ST-g-PS, H-ST, and H-ST-LA-IL reached equilibrium within 90 min and showed a good general diffusion model kinetic trend (R 2 >0.9). Among them, H-ST-LA-IL has a higher equilibrium formaldehyde adsorption capacity of 13.5 mg / g, while the equilibrium formaldehyde adsorption capacities of H-ST-g-PS and H-ST are only 6.9 mg / g and 4.5 mg / g.
[0097] Figure 6 The adsorption kinetics calculated in the results show that the adsorption rate of formaldehyde by H-ST-LA-IL is higher, which is 3.22 and 4.33 times that of H-ST-g-PS and H-ST, respectively. This is attributed to the high specific surface area of H-ST-LA-IL and the alkaline ionic liquid adsorption microenvironment.
[0098] The examples given in the present invention are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a starch-based ionic porous polymer, characterized in that: The method comprises the following steps: (1) Preparation of lactic acid-starch: gelatinize starch at a certain temperature, add lactic acid and catalyst zinc acetate to continue the reaction for 10-12 hours, cool after the reaction is completed, add ethanol to precipitate a white solid, filter, extract, and freeze-dry to obtain lactic acid-starch; (2) Preparation of ionic liquid functionalized starch: under N2 atmosphere, the lactic acid-starch, ionic liquid and initiator azobisisobutyronitrile obtained in (1) were dispersed into aqueous solution and stirred for reaction for 20-24 hours. After the reaction was completed and cooled, ethanol was added to precipitate a white solid, which was filtered and freeze-dried to obtain ionic liquid functionalized starch. (3) Preparation of starch-based ionic porous polymer: Under N2 atmosphere protection, the ionic liquid functionalized starch and cross-linking agent obtained in (2) are added to 1,2-dichloroethane, and then anhydrous FeCl3 catalyst is added. After stirring at 40-45°C for 2-3h, the temperature is raised to 80-85°C and the reaction is continued for 16-20h. After the reaction is completed and cooled, the starch-based ionic porous polymer is obtained by filtration, extraction, and vacuum drying.
2. The method for preparing the starch-based ionic porous polymer according to claim 1, characterized in that: The starch in step (1) is tapioca starch, sweet potato starch or corn starch.
3. The method for preparing the starch-based ionic porous polymer according to claim 1, characterized in that: In the step (1), the mass ratio of starch, lactic acid and catalyst zinc acetate is 1:0.2-3:0.02-0.
1.
4. The method for preparing the starch-based ionic porous polymer according to claim 1, characterized in that: In the step (1), the starch is first gelatinized at 70-85° C. for 30-60 min.
5. The method for preparing the starch-based ionic porous polymer according to claim 1, characterized in that: The ionic liquid in step (2) is any one of 1-vinyl-3-butylimidazolium bromide [C4VIm][Br], 1-vinyl-3-butylimidazolium tetrafluoroborate [C4VIm][BF4], 1-vinyl-3-butylimidazolium hexafluorophosphate [C4VIm][PF6] and 1-vinyl-3-butylimidazolium acetate [C4VIm][OAc].
6. The method for preparing the starch-based ionic porous polymer according to claim 1, characterized in that: In the step (2), the mass ratio of lactic acid-starch, ionic liquid and initiator azobisisobutyronitrile is 1:1-5:0.02-0.
1.
7. The method for preparing the starch-based ionic porous polymer according to claim 1, characterized in that: The cross-linking agent in step (3) is biphenyl benzyl dichloride or p-dichlorobenzyl.
8. The method for preparing the starch-based ionic porous polymer according to claim 1, characterized in that: In the step (3), the mass ratio of the ionic liquid functionalized starch, the crosslinking agent and the catalyst anhydrous FeCl3 is 1:0.5-3:0.2-2.
9. The method for preparing the starch-based ionic porous polymer according to claim 1, characterized in that: In the step (3), the plastochemical ratio of the ionic liquid functionalized starch to 1,2-dichloroethane is 1:50-150.
10. Use of the starch-based ionic porous polymer prepared by the method according to any one of claims 1 to 9, characterized in that: Application of starch-based ionic porous polymers in aldehyde VOCs adsorbents.
Citation Information
Patent Citations
Starch-or-cellulose-based polymeric porous adsorption resin and preparation method thereof
CN110003390A
Polyimidazole ionic liquid modified porous cellulose as well as preparation method and application thereof
CN118373942A
Process for preparing mesoporous carbon material
EP3872030A1
Porous cyclodextrin polymer
US20210147600A1